ANALISIS PERATAAN LABA TERHADAP HARGA SAHAMPADA PERUSAHAAN PERBANKAN YANG GO PUBLIK - Kristiana Prariwi (2013)
Income smoothing is an accounting practice that is often applied by the company manager. Measures income smoothing considered as action. Commonly done by management to achieve specific goals. However, income smoothing practice was heavily criticized by many people because it can cause harm. This research was conducted to examine the effect of income smoothing variables on stock prices. The population number of 32 banking companies that go public. Data were obtained from published financial statements from 2006 to 2011 and the share price calculated using a price earnings ratio of the stock price after 7 days, in the published financial statements. Total sample Obtained of 16 firms after sampling is purposive sampling. The analysis method used is a simple linear regression and hypothesis testing using t-test statistics with a confidence level of 5%. The results show that income smoothing effect on stock prices